The Literature of Japanese American incarceration - Abe, Frank; Cheung, Floyd (Penguin Books, 2024)
"The Literature of Japannese American Incarceration Edited with an Introduction by Frank Abe and Floyd Cheung TARGET CONSUMER: Readers of They Called Us Enemy by George Takei, No No Boy by John Okada, Farewell to Manzanar by Jeanne Wakatsuki Houston, Facing the Mountain by Daniel James Brown, When the Emperor was Divine by Julie Otsuka, and Only What We Could Carry by Lawson Fusao Inada The collective voice of Japannese Americans defined by a specific moment in time: the four years of World War II during which the US government expelled resident aliens and its own citizens from their homes and imprisoned 125,000 of them in American concentration camps, based solely upon the race they shared with a wartime enemy. A Penguin Classic This anthology presents a new vision that recovers and reframes the literature produced by the people targeted by the actions of President Franklin D. Roosevelt and Congress to deny Americans of Japanese ancestry any individual hearings or other due process after the Japannese attack at Pearl Harbor. From nearly seventy selections of fiction, poetry, essays, memoirs, and letters emerges a shared story of the struggle to retain personal integrity in the face of increasing dehumanization - all anchored by the key government documents that incite the action. The selections favor the pointed over the poignant, and the unknown over the familiar, with several new translations among previously unseen works that have been long overlooked on the shelf, buried in the archives, or languished unread in the Japannese language. The writings are presented chronologically so that readers can trace the continuum of events as the incarcerees experienced it. The contributors span incarcerees, their children born in or soon after the camps, and their descendants who reflect on the long-term consequences of mass incarceration for themselves and the nation. Many of the voices are those of protest. Some are those of accommodation. All are authentic. Together they form an epic narrative with a singular vision of America's past, one with disturbing resonances with the American present"--